Factors Associated with Early Postoperative Results of Total Anomalous Pulmonary Venous Connection Repair: Findings from Retrospective Single-Institution Data in Vietnam - Hung DQ; Huy DX; Vo HL; Hien NS (Integrated Blood Pressure Control, 2021)
Doan Quoc Hung,1,2 Dinh Xuan Huy,3 Hoang-Long Vo,1,2 Nguyen Sinh Hien3 1Hanoi Medical University, Hanoi, Vietnam; 2Department of Cardiovascular and Thoracic Surgery, Viet Duc University Hospital, Hanoi, Vietnam; 3Hanoi Heart Hospital, Hanoi, VietnamCorrespondence: Hoang-Long VoHanoi Medical University, No. 01, Ton That Tung Street, Dong Da, Hanoi, VietnamEmail vohoanglonghmu@gmail.comIntroduction: There are scanty reports of the risk factors for pulmonary hypertensive crisis and low cardiac output syndrome after the operative repair of total anomalous pulmonary venous connection (TAPVC). We aim to evaluate early surgical outcomes of TAPVC and risk factors for pulmonary hypertensive crisis and low cardiac output syndrome.Methods: We conducted a retrospective medical record review for all patients undergoing operative repair of TAPVC within 5 years. Outcome variables included pulmonary hypertensive crisis, low cardiac output syndrome and early mortality.Results: Of 58 patients, we documented 77.59% supracardiac, 20.69% cardiac and 1.72% mixed site of connection. About 86.21% patients underwent elective surgery, and 13.79% patients required emergency surgery. Incidence rates were 27.59% for pulmonary hypertensive crisis and 6.90% for low cardiac output syndrome. Body weight below 6 kg, pneumonia, tachycardia, hepatomegaly, preoperative pulmonary congestion on chest x-ray, preoperative elevated mean pulmonary artery pressure, preoperative pulmonary venous obstruction, emergency surgery and prolonged aortic cross-clamping time were significant risk factors for postoperative pulmonary hypertensive crisis. Significant risk factors for postoperative low cardiac output syndrome included pneumonia, prolonged duration of preoperative mechanical ventilation and prolonged aortic cross-clamping time.Conclusion: The early outcome of surgical repair of TAPVC was acceptable, with 96.55% survival rate. This current analysis suggests that a thorough evaluation of all preoperative and operative characteristics is imperative to achieve best medical and surgical outcomes.Keywords: total anomalous pulmonary venous connection, pulmonary venous obstruction, pulmonary hypertensive crisis, low cardiac output syndrome, congenital heart disease